2021
DOI: 10.1017/jgc.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Role of peer support in competitive classroom climates: Focusing on the mediation effect of academic hatred in the JD-R model

Abstract: This study aimed to verify the different effects of peer support on academic hatred depending on the levels of teachers’ academic pressure. Additionally, we examined the effects of academic hatred on academic burnout and engagement by applying the job demand-resources (JD-R) model. Data were collected from 43 classes at 8 high schools (N = 1015, 94.2% response rate, 57.3% women) in South Korea. The results of a multigroup analysis were as follows: (1) peer support served as an important resource in classrooms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…When the relevant literature is examined, it has been seen that some studies support these results. Accordingly, burnout and school commitment (Özdemir, 2015;Pilkauskaite-Valickiene et al, 2011;Shin & Yu, 2014;Şahan & Duy, 2017), academic motivation (Avara, 2015;Özdemir, 2015;Seçer & Öztürk, 2015), academic pressure (Shin, 2020), problem solving skills (Kim et al, 2017;Luo et al, 2016;Shin et al, 2012), and peer relationships (Kim, Lee, Lee, An & Lee, 2018;Kiuru et al, 2008;Laursen et al, 2010;Lee, Lee & Lee, 2021;Rimpelä et al, 2020) were found to have significant relationships. It has been determined that the predictive variables in the Hierarchical Multiple Regression Analysis applied in the study explain approximately 50% of the total variance regarding school burnout scores.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…When the relevant literature is examined, it has been seen that some studies support these results. Accordingly, burnout and school commitment (Özdemir, 2015;Pilkauskaite-Valickiene et al, 2011;Shin & Yu, 2014;Şahan & Duy, 2017), academic motivation (Avara, 2015;Özdemir, 2015;Seçer & Öztürk, 2015), academic pressure (Shin, 2020), problem solving skills (Kim et al, 2017;Luo et al, 2016;Shin et al, 2012), and peer relationships (Kim, Lee, Lee, An & Lee, 2018;Kiuru et al, 2008;Laursen et al, 2010;Lee, Lee & Lee, 2021;Rimpelä et al, 2020) were found to have significant relationships. It has been determined that the predictive variables in the Hierarchical Multiple Regression Analysis applied in the study explain approximately 50% of the total variance regarding school burnout scores.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…(2022) showed that institutional incentives and resources positively predicted academic engagement. Moreover, Lee et al. (2021) evidenced that peer support was a crucial resource in competitive classroom climates, as it lessened academic hatred, that in turn, reduced academic burnout and improved academic engagement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, Sormani et al (2022) showed that institutional incentives and resources positively predicted academic engagement. Moreover, Lee et al (2021) evidenced that peer support was a crucial resource in competitive classroom climates, as it lessened academic hatred, that in turn, reduced academic burnout and improved academic engagement. Dixit and Upadhyay (2021), in a higher education setting, showed that work engagement was a mediator in the relationship between job resources and demands and innovative work behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations